Phaleria macrocarpa reduces glomerular growth factor expression in alloxan-induced diabetic rats - Sulistyonongrum Evy; Setiawati Setiawati (Universa Medicina, 2013)
BACKGROUNDDiabetic nephropathy (DN) is the most serious complication of diabetes, causingend-stage renal disease throughout the world. Recent studies have reported adirect role of vascular endothelial growth factor (VEGF) and transforming growthfactor-â (TGF-â) in DN pathogenesis. VEGF and TGF-â are expressed early inglomeruli in response to hyperglycemia. Active substances of Phaleriamacrocarpa (PM) pericarp are known to have nephroprotective effects. Thisstudy aimed to evaluate the effects of Phaleria macrocarpa (Scheff.) Boerlpericarp extract on VEGF and TGF-â expression in alloxan-induced diabetic rats.METHODSAn experimental study was conducted on twenty five male albino (SpragueDawley) rats divided into five groups (of five each): normal control; diabetic;diabetic + metformin 100 mg/kgBW; diabetic + methanolic PM extract 250 mg/kgBW; and diabetic + aqueous PM extract 250 mg/kgBW. Diabetes was inducedby alloxan monohydrate 150 mg/BW intraperitoneally. Treatment was given for3 weeks. VEGF and TGF-â expression analysis was performed by means ofimmunohistochemical technique. Differences between groups were assessedby one-way ANOVA.RESULTSVEGF expression in the PM extract group was significantly lower than that in thediabetic group and even metformin group (p<0.01). TGF-â expression inmethanolic PM extract group was significantly lower than in diabetic andmetformin group (p<0.01), but aqueous PM extract group only showedsignificancy when compared with diabetic group (p< 0.01).CONCLUSIONSPhaleria macrocarpa pericarp extract reduces glomerular expression of TGF-âand VEGF in alloxan-induced diabetic rats.